Rapid characterisation of bioaerosols from rural, industrial and agricultural environments - Shuaib, Mahmud (Cranfield University, 2018)
The aim of this study was twofold: 1) to compare two different bio aerosol sampling techniques, polycarbonate filters, and Coriolis®µ and 2) characterise bioaerosols by the analysis of PLFA biomarkers in order to identify the microbial communities present in contrasting outdoor environments (a WWTP, compost facility, three different farms, 2 parks and an urban area). Sample collection efficiency was 34% greater when collecting air samples with polycarbonate filters than with Coriolis in recreational parks where there is a low microbial activity. Areas with higher diversity index in the microbial communities corresponded to the ones with a higher amount of PLFAs such as the WWTP and the composting facility (1.986 and 1.624 respectively). Actinomycetes were only found in industrial and urban areas. No site specific PLFA was found and only the PLFA profile from the composting facility was different from the rest of the sites. This chemical approach therefore might not be enough to differentiate different bioaerosol profiles from outdoor environments.
Keywords: Biomarker'; 'bioaerosols'; 'bioaerosol exposures'; 'Atmospheric Aerosols'; 'Atmospheric Sciences'